Harnessing Cold Plasma: An Innovative Strategy for Managing Postharvest Fungal Infections in Plants - C. Shanmugaraj; V. Jaiganesh; H.M. Akshay Kumar; M.K. Biswas (Archives of Current Research International, 2024)
Researchers in plant pathology in recent times; have faced obstacles in finding chemical-free methods to combat postharvest fungal infections on a large scale. While conventional approaches like heat treatments have been utilized, they often present drawbacks such as altering food quality or causing harm to the environment. An encouraging alternative is a cold plasma, which consists of a blend of gas-derived atoms, excited molecules, and charged particles. Unlike alternative treatments, cold plasma has demonstrated no adverse effects on fresh produce or the environment. This review delves into the potential of cold plasma technology in managing postharvest fungal diseases, offering insights into plasma generation systems and examining both in vivo and in vitro studies. By evaluating the benefits, constraints, and current research gaps, this review seeks to guide for implementation of cold plasma technology in commercial settings.